COMMUNITY PERCEPTIONS OF EARLY ADULT DOWN SYNDROME A SYSTEMATIC REVIEW - Nurzaki Alhafiz; wazirotus sakinah; Agus Mursidi (SOSIOEDUKASI, 2024)
Background: society's perception of Down syndrome in early working adults . Objective: to determine the public's perception of Down syndrome in early adulthood. Method: the source of the article used was obtained from a search via Google Scholar. A literature search with the same theme contained 17,700 articles and filtering was carried out according to the theme, including 17 articles. Article searches are limited from 2019-2024. After the article is obtained, the article is reviewed until it reaches the stage of creating a systematic review. The keywords used in the article search are " Perception" "Public" "Down Syndrome" "Early Adulthood" . Results: society's perception of Down syndrome in early adulthood is shrouded in stigma and bad perceptions even occur in their families. Conclusion: Individuals with Down syndrome , from children to adults, are part of society. Even though they are often seen with stigma and negative perceptions because of their physical differences, they still need support and understanding from their surrounding environment. Their enthusiasm and adaptability allow them to live and participate in daily activities like any other individual